THE RELATIONSHIP OF SERUM VITAMIN 25(OH)D3-LEVELS WITH WOMEN OBESITY - AL- Ardhi, Ghadeer Hamid (PT. Antis International Publisher, 2025)
Objectives: This paper aims to evaluate the relationship between vitamin D3 levels and obesity in adult women compared to normal weight women. Method: Ninety-six (96) women them age around (20-50) years were collected and classified into three groups based on BMI categories. ELISA kit was used to measure vitamin D3 levels in serum of blood. Results: The results showed significantly lower vitamin D3 levels (15.28±1.13) in obese and overweight women (22.46 ±1.31) compared to normal weight group (34.40 ±2.43) at p≤ 0.05, and a negative significant correlation between vitamin25(OH) D3 levels and BMI in obese women. Novelty: This finding suggested that vitamin D3 deficiency in obese women may be due to its storage in adipose tissue which reduces its levels in the bloodstream. In addition to other different mechanism. More studies are required for detect the complex interchange between vitamin D3 and obesity to know more about the biological mechanism of action.